2008
DOI: 10.3858/emm.2008.40.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel anti-human TNF-α murine monoclonal antibody with high binding affinity and neutralizing activity

Abstract: In order to develop an anti-human TNF-α mAb, mice were immunized with recombinant human TNF-α. A murine mAb, TSK114, which showed the highest binding activity for human TNF-α was selected and characterized. TSK114 specifically bound to human TNF-α without cross-reactivity with the homologous murine TNF-α and human TNF-β. TSK114 was found to be of IgG1 isotype with κ light chain. The nucleotide sequences of the variable regions of TSK114 heavy and light chains were determined and analyzed for the usage of gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 27 publications
6
24
0
Order By: Relevance
“…Three days after the last injection, spleen cells from the immunized mice were fused with murine myeloma Sp2/O cells (American Type Culture Collection) in the presence of 50% (w/v) polyethylene glycol 1500 (Roche; ref. 25). From the screening of hybridoma supernatants against DR4-ECD using ELISA, 10 positive hybridomas were isolated ( Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three days after the last injection, spleen cells from the immunized mice were fused with murine myeloma Sp2/O cells (American Type Culture Collection) in the presence of 50% (w/v) polyethylene glycol 1500 (Roche; ref. 25). From the screening of hybridoma supernatants against DR4-ECD using ELISA, 10 positive hybridomas were isolated ( Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…AY4 was purified from the cell supernatant by Protein A-Sepharose 4 Fast Flow (Pharmacia; ref. 25). Cloning of AY4 gene from the hybridoma by reverse transcription-PCR and then sequence analysis revealed that the subclass of AY4 mAb was IgG1 for heavy chain and κ for light chain.…”
Section: Methodsmentioning
confidence: 99%
“…The binding association rate constant (k on ) of infliximab was fixed to 10 5 M 21 × S 21 (Kim et al, 2007;Song et al, 2008).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Of the 4 TNFα binding KD variants, biological activity assays using a human TNFα-responsive WEHI 164 cell bioassay (20,23) revealed that only KDT26 neutralized TNFα-mediated cytotoxicity in a concentration-dependent manner, showing IC 50 (50% inhibitory concentration) of ∼0.8 μM (Fig. 4A).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro and in vivo neutralizing activities of PgnKD2, the KD variants, KDT26-Fc, and/or infliximab were measured against human TNFα-induced cytotoxicity using mouse WEHI 164 cells (ATCC) and TNFα-induced lethality in C57BL/6 mice (Orientbio), as described previously (20,23,24).…”
Section: Methodsmentioning
confidence: 99%